Magnetic field statistical characteristics and their relation to the geological structure of quartz-gold deposits - Erofeev L. Ya. Leonid Yakovlevich (2014, 2014)
The analysis of experimental data obtained from typical gold deposits in Kuznetskoe Ala Tau and Transbaikal showed that density distribution of increment induction is subjected to the logarithmic normal distribution law, the asymmetry of which, reflects ore prospect metamorphism grade. The spectral dispersion density decreases at average, inversely proportional to square frequency. Local dispersion density increases in low dispersion density background can be in individual ore-bearing zones, which in its turn are associated ore bodies . The magnetic field is characterized by abnormal anisotropy, reflecting the development of diversified elements of the formation structure. Normal entropy induction variations exceeds 0.8, indicating the heterogeneous petromagnetic zone structure. The paper includes field observation technique recommendations and interpretation results.